Factors associated with the use of assistive technologies in elders in their home environments - Luipa Michele Silva; Ana Carolina de Souza; Jack Roberto Silva Fhon; Rosalina Aparecida Partezani Rodrigues; Larissa Azevedo dos Santos; Maria Fernanda Costa Troncha Gomes (Universidade Federal do Ceará, 2022)
Objective: to identify the factors associated with the use of assistive technologies by elders in their home environment. Methods: cross-sectional, analytical, and exploratory study with 127 elders capable of answering the data collection instruments. Analyses were carried out using Student's t, Pearson's correlation, and linear regression. Results: in regard to the type of assistive device used, 52.8% of interviewees used orthoses or prostheses, 48.8% used shower chairs, and 47.2% used wheelchairs. In the comparative analysis of the means, there was a statistically significant association between basic daily life activities and cognitive state. In basic daily life activities (r=0.52), as the score of the elderly in Katz's Index increases, the use of assistive devices also increases. In turn, as the Lawton and Brody Scale (r=-0.279) increases, the number of devices decreases. Conclusion: the prevalence of elders who use assistive devices in their homes was high, showing a direct association with their functional capacity and their performance of basic and instrumental daily life activities. Contributions to practice: this research contributes for the organization of elderly assistance by nursing workers, encouraging elder independence and autonomy.